PEMBUATAN PORTAL WEBSITE SEKOLAH SMA NEGERI 1 SUNGAILIAT SEBAGAI MEDIA INFORMASI - Riki Afriansyah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
KThe existence of a school website is very important to disseminate information needed for schools, teachers, students and the community. With the website, information can be easily managed by the school. For example, important announcement information, the school operator can input the information through the website portal so that the public can read the information effectively and efficiently without having to come to school. In addition, the public can communicate with school operators through the chat feature and download the required documents via the web. Another feature is the photo album and video activities carried out by the school as a promotional media as well as the features that are connected to social networking services namely Instagram. The results of the final interview this activity was obtained that this website provides many benefits for the community as well as ease in managing information systems by operator.